2015
DOI: 10.1002/pssb.201451562
|View full text |Cite
|
Sign up to set email alerts
|

Thickness and growth condition dependence of crystallinity in semipolar (20–21) GaN films grown on (22–43) patterned sapphire substrates

Abstract: We have investigated the crystalline morphology such as lattice plane curvature and lattice plane tilting in (20-21) GaN films on (22-43) patterned sapphire substrates (PSS) by using X-ray rocking curve (XRC) measurements. The results of the symmetric XRC for the GaN (20-21) plane showed anisotropic lattice plane curvature between the [À1014] and [À12-10] directions. This is due to the large difference of the thermal expansion coefficient in the [0001] direction between GaN and sapphire. From the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The ð000 1Þ planes have also been observed in selective area MOVPE of GaN on the nonpolar and semipolar planes. [16][17][18][19][20] It has been pointed out that the −c growth promotes the inclusion of stacking faults. 20) To confirm whether this also occurs in our samples, CL mapping was performed for a sample with FF = 0.25, which has a structure similar to sample E, but the inverted trapezoids do not coalesce.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ð000 1Þ planes have also been observed in selective area MOVPE of GaN on the nonpolar and semipolar planes. [16][17][18][19][20] It has been pointed out that the −c growth promotes the inclusion of stacking faults. 20) To confirm whether this also occurs in our samples, CL mapping was performed for a sample with FF = 0.25, which has a structure similar to sample E, but the inverted trapezoids do not coalesce.…”
mentioning
confidence: 99%
“…[16][17][18][19][20] It has been pointed out that the −c growth promotes the inclusion of stacking faults. 20) To confirm whether this also occurs in our samples, CL mapping was performed for a sample with FF = 0.25, which has a structure similar to sample E, but the inverted trapezoids do not coalesce. It was found that there were no dark lines in the areas corresponding to the −c growth front, which suggested the absence of stacking faults.…”
mentioning
confidence: 99%
“…By comparing samples A and B, since the HVPE-GaN growth conditions were the same for both samples, the reduction in BSF width was considered to be due to the use of the MOVPE-GaN template with the −c-plane-suppressed growth. 17) Many threading dislocations were also observed in both samples. From the results of g · b (b: Burgers vector) analysis, the Burgers vectors of these dislocations can be identified to be of the (a + c)-type.…”
Section: Defect Distribution In ð20mentioning
confidence: 86%
“…In this study, two types of MOVPE-GaN templates were prepared; either normal growth or −c-direction-suppressed growth was selected by tuning the V=III ratio and growth temperature appropriately. 17) After fabricating MOVPE-GaN templates, a 40-µm-thick HVPE-GaN film was grown on each MOVPE-GaN template. The HVPE-GaN film was grown at a V=III ratio of 10 at 1040 °C.…”
Section: A ð20 "mentioning
confidence: 99%